Contrasting Timing of Virological Relapse After Discontinuation of Tenofovir or Entecavir in Hepatitis B e Antigen–Negative Patients. (9th June 2018) - Höner zu Siederdissen, Christoph; Hui, Aric Josun; Sukeepaisarnjaroen, Wattana; Tangkijvanich, Pisit; Su, Wei Wen; Nieto, Gerardo Enrique Guillén; Gineste, Paul; Nitcheu, Josianne; Crabé, Sandrine; Stepien, Sandrine; Manns, Michael P; Trépo, Christian; et al.
Abstract: Stopping long-term nucleos(t)ide analogue therapy increases hepatitis B virus (HBV) surface antigen (HBsAg) loss rates in HBV e antigen (HBeAg)–negative patients. Viral rebound may induce immune responses facilitating functional cure. We analyzed which factors are associated with timing of virological relapse in 220 Asian HBeAg-negative patients from the prospective ABX203 vaccine study. Unexpectedly, only the type of antiviral therapy was significantly associated with early virological relapse, defined as an HBV DNA load of >2000 IU/mL until week 12, and relapse occurred earlier in patients treated with tenofovir versus those treated with entecavir (median time, 6 vs 24 weeks; P < .0001). This should be considered for future trials and monitoring of patients after treatment discontinuation.